Sammellager Bogusze (November 2, 1942 – January 3, 1943) as an example of a transitional collective camp in the Operation “Reinhardt” in the Bialystok District - Stefan Marcinkiewicz (Zagłada Żydów)
The article presents the origins, functioning and the liquidation of Sammellager Bogusze, one of five collective transit camps in the Bialystok District, intended for the Jewish population under the „Reinhardt” action. It detained Jews from Augustów, Grajewo, Rajgród, Goniadz, Stawiska, Szczuczyn, Trzcianne and the camp in Milewo. The author determined that about 7.5 thousand Jews were imprisoned in Sammellager Bogusze. Of these, 4.5 thousand were murdered at Treblinka extermination center (December 16, 1942) and 2 thousand at Auschwitz II Birkenau (January 7, 1943). Approximately 1 thousand died on the spot and are buried in the camp cemetery in Bogusze